2023
DOI: 10.1002/ejoc.202300463
|View full text |Cite
|
Sign up to set email alerts
|

Construction of β‐Phenylalanine Derivatives through Pd‐Catalyzed, C(sp2)−H (ortho) Functionalization

Abstract: This paper describes the Pd(II)‐catalyzed, picolinamide‐directing‐group‐aided C(sp2)−H (ortho) functionalization of racemic and enantiopure β‐phenylalanines and 3‐amino‐3‐phenylpropanols (1,3‐amino alcohols). The C(sp2)−H (ortho) functionalizations including arylation, bromination, iodination, and alkoxylation were attempted. The C(sp2)−H (ortho) arylation reactions gave biaryl or terphenyl‐type β‐phenylalanine scaffolds, halogenation and methoxylation reactions gave ortho C−H halogenated or methoxylated β‐phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 157 publications
0
1
0
Order By: Relevance
“…Miura et al revealed [81] two examples of copper-mediated dehydrogenative biaryl coupling of the pyrene core using the picolinamide bidentate directing group-assisted C-H functionalization strategy [81][82][83][84][85][86][87][88][89]. Substrate N-(pyren-1-yl)picolinamide 22a was treated with the azole derivatives 22aa and 22ab (2 equiv) in the presence of Cu(OAc) 2 (3 equiv) and PivOH (1 equiv) in mesitylene at 165 • C for 4 h under a nitrogen atmosphere (Scheme 15).…”
Section: Directing Group-assisted C-h Functionalization Of the C10 Po...mentioning
confidence: 99%
“…Miura et al revealed [81] two examples of copper-mediated dehydrogenative biaryl coupling of the pyrene core using the picolinamide bidentate directing group-assisted C-H functionalization strategy [81][82][83][84][85][86][87][88][89]. Substrate N-(pyren-1-yl)picolinamide 22a was treated with the azole derivatives 22aa and 22ab (2 equiv) in the presence of Cu(OAc) 2 (3 equiv) and PivOH (1 equiv) in mesitylene at 165 • C for 4 h under a nitrogen atmosphere (Scheme 15).…”
Section: Directing Group-assisted C-h Functionalization Of the C10 Po...mentioning
confidence: 99%